Thermal studies and influence of the thermal decomposition on dielectric properties of a new coumarin copolymers - Biryan, Fatih; Pihtili, Guzin; Demirelli, Kadir (Springer, 2020)
In this study, firstly 7-hydroxy-4-chloroethyl coumarin compound was synthesized in accordance with the literature (Peterson et al. in Macromol Chem Phys 202: 775-784, 2001). Then, this compound was reacted with acryloyl chloride to form the 4-(chloromethyl)-2-oxo-2H chromen-7-yl-acrylate) monomer. A series of copolymers were prepared using this monomer and n-butyl acrylate monomer. TGA analysis system was used to examine the thermal properties of homopolymers and copolymers. The activation energies were calculated for thermal decomposition of homopolymer and certain copolymers according to Flynn-Wall-Ozawa method. TGA measurements were taken at different heating rates and given comparatively. The glass transition temperatures of the copolymers were determined by DSC analysis and these results were given comparatively. For investigating the dielectric properties of copolymers, dielectric constant, dielectric loss factor, and ac conductivity values were calculated in the range of 100 Hz-20 kHz frequencies. The results were plotted as a function of frequency. In addition, dielectric behaviors of residues were determined after heating to the first decay temperature of the two-stage decay polymers and compared with the first states.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: Coumarin; Thermal study; Thermal decomposition